THE EFFECT OF VARIABILITY IN NET PRIMARY PRODUCTIVITY ON THE NUMBER OF CATCHES OF SARDINELLA LEMURU IN THE BALI STRAIT - Maulana, Denna
Tropical fisheries and marine ecosystems in the Bali Strait are facing significant challenges due to climate change, with a specific focus on the impact it has on Sardinella lemuru (S. lemuru), a dominant species in this region. Sardinella lemuru contributes substantially to the small pelagic fisheries, accounting for 16.2% of the total production in Fisheries Management Area (FMA) 573. To understand the effects of climate-induced changes on Sardinella lemuru, a comprehensive study was conducted from 2003 to 2022. The study utilized the Vertically Generalized Production Model (VGPM) to estimate net primary productivity. This method relies on data such as surface chlorophyll-a levels, sea surface temperature, and Photosynthetically Active Radiation (PAR), which were obtained from MODIS satellite imagery. The Maximum Sustainable Yield (MSY) is a crucial benchmark for sustainable fisheries management, and the Catch Per Unit Effort (CPUE) is a key factor in determining the maximum sustainable catch. The research uncovered a strong correlation between marine productivity variations and monsoon patterns in the Bali Strait. Productivity reached its peak during the east monsoon and hit its lowest point during the west monsoon, with average values of 1947.81 mgC.m-2.day-1 and 593.81 mgC.m-2.day-1, respectively. Interestingly, the study also highlighted the influence of the interannual climate phenomenon known as the Indian Ocean Dipole (IOD) on marine productivity, which was found to be more substantial than the impact of the El-Nino Southern Oscillation (ENSO). During IOD+ (-) events, marine productivity experienced positive (negative) anomalies, which in turn affected the catch of Sardinella lemuru. The study observed a significant increase in Sardinella lemuru catch, rising from 140.1 tons to 6210.4 tons over the study period. The catch of Sardinella lemuru at the Pengambengan Fishery Harbor has experienced overfishing which has resulted in a decline in catches in 2017 and 2018 to only 76.5 tons/year. The optimal catch based on the Schaefer model is around 4066.22 fleets with 3.15 tons/fleet.